Ion Channels in Health and Sickness - Fatima Shad, Kaneez (IntechOpen, 2018)
Ion channels are proteins that make pores in the membranes of excitable cells present both in the brain and the body. These cells are not only responsible for converting chemical and mechanical stimuli into the electrical signals but are also liable for monitoring vital functions. All our activities, from the blinking of our eyes to the beating of our heart and all our senses from smell to sight, touch, taste and hearing are regulated by the ion channels. This book will take us on an expedition describing the role of ion channels in congenital and acquired diseases and the challenges and limitations scientist are facing in the development of drugs targeting these membrane proteins.